2005
DOI: 10.1021/jp045560p
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemical Studies of Mononuclear Zinc Species of Hydration and Hydrolysis

Abstract: Optimal geometries, charge distributions, bond analysis, changes of Gibbs free energy, entropies and enthalpies of hydration, and hydrolysis reactions for mononuclear species of Zn 2+ including hydrated and hydrolysis complexes were investigated using quantum chemical calculations in the gas phase. Optimized geometrical structures showed that the stable hydrated and hydrolysis zinc species without outer-sphere water molecules . Results of NPA (Natural Population Analysis) indicated that the charge on the Zn at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 21 publications
7
34
0
Order By: Relevance
“…To eliminate boundary effect and reduce charge of the clusters, the hanging bonds of O atoms were saturated with H atoms. 5,15,16 Geometries were predicted using 6-31+G(d) basis set for O, H, 6-311+G(d) basis set for As, and LANL2DZ relativistic effective core potential (RECP) basis set for Ti atoms. 14,15 It was reported that the surface of anatase TiO 2 particle predominantly consisted of (101), (100), and (001) crystal plane, 17,18 and the exposition of crystal plane depended on the synthetic technique.…”
Section: Theoretical and Experimental Methodsmentioning
confidence: 99%
“…To eliminate boundary effect and reduce charge of the clusters, the hanging bonds of O atoms were saturated with H atoms. 5,15,16 Geometries were predicted using 6-31+G(d) basis set for O, H, 6-311+G(d) basis set for As, and LANL2DZ relativistic effective core potential (RECP) basis set for Ti atoms. 14,15 It was reported that the surface of anatase TiO 2 particle predominantly consisted of (101), (100), and (001) crystal plane, 17,18 and the exposition of crystal plane depended on the synthetic technique.…”
Section: Theoretical and Experimental Methodsmentioning
confidence: 99%
“…It has been reported that the most common coordination geometries of hydrous Zn(II) are octahedron (i.e., Zn(H 2 O) 2+ 6 ) with a Zn-O bond length of 2.07-2.18 Å and tetrahedron (i.e., ZnO(s), Zn(OH) 2− 4 ) with a Zn-O bond length of 1.92-1.99 Å [45]. Zhu and Pan [46] reported that in acidic solutions (pH 6.9) Zn 2+ (aq) is present in the form of octahedron with an average Zn-O bond length of 2.08 Å. As shown in Table 3, the average Zn-O bond length of the three samples is 1.98 ± 0.01 Å, and the average coordination number is 4.3 ± 0.02 Å.…”
Section: The Microscopic Structure Of Adsorbed Zn(ii)mentioning
confidence: 99%
“…This difference between experimental and theoretical values has been attributed to the theoretical underestimation of solvent effect from outer-sphere water molecules. 39 However, we expect that this artifact does not affect the relative stability of the adsorption modes and their coordination properties.…”
Section: X-ray Absorption Fine Structure Measurement and Datamentioning
confidence: 97%